How to Reduce Customer Struggles in Online Shopping in China - Wang, Fan (2012)
This paper attempts to provide efficient approaches on reducing customer struggles in online shopping. It appears that online retailing in China needs more improvements based on the customer-centred perspective. Customer struggles relate to physical and psychological flounders, such as unqualified products, unsatisfied services, loss of money and information leakage. Factors that affect customer struggles online include price, diversity of products, quality of items, quality of services, and communication with online sellers. Correspondingly, the strategies and methods online retailers adopted should focus on these aspects. Furthermore, in order to understand the uniqueness of Chinese online shopping market, this paper introduces three typical online retailers in China--Taobao, Dangdang and Vancl. It is found that although these online firms have done well at product aspect, they need more understanding on customer struggles and make improvement in service quality.